RNase III cleaves vesicular stomatitis virus genome-length RNAs but fails to cleave viral mRNA's. - Wertz, G W (1979)
The procaryotic RNA processing enzyme RNase III (endoribonuclease III [EC 3.1.4.24]) was used to probe vesicular stomatitis virus (VSV) RNAs for specific sites that could be recognized and cleaved. The effect of the enzyme on the RNAs was monitored by measuring their subsequent migration in denaturing agarose-urea gels. VSV virion RNA (negative strand; Mr, 4 X 10(6)) was cleaved by the enzyme to yield a set of discrete fragments which ranged on size from 3.5 X 10(6) to 0.2 X 10(6) daltons. The cleavage was a function of enzyme concentration, salt concentration, and time. A maximum of 20 to 22 fragments was generated under conditions of low enzyme concentration or short times of incubation. VSV genome-length intracellular RNA of both + and - polarity was also cleaved by RNase III. In contrast to the findings with virion-length RNA, however, the migration rates of VSV mRNA's purified by chromatography on polyuridylic acid-Sepharose were unaffected by treatment with RNase III. These results show that specific sites in the virion RNA and its full-length complement can be recognized by RNase III. Sites of this type are not present in the polyadenylic acid-containing mRNA, however.